Higher education in the fight against poverty from the capabilities approach: The case of Spain - Roberto Sanz; José Alfredo Peris; Juan Escámez (Journal of Innovation & Knowledge (JIK), 2017)
This article describes relative poverty in Spain in relation to the other States in the European Union, following the European indicator AROPE. The official data provided by the National Statistical Institute of Spain and by Eurostat, refer to the year 2014 (the last one for which definitive data are available is 2015). Given the relative poverty of Spanish population, the failure of conventional economic theories, which conceive social development as GDP growth, is clear, and it is argued in favour of the human capabilities approach as a more adequate option for development, from a theoretical-practical point of view, for the reduction and/or eradication of poverty, as well as the appropriateness of a new conception of Higher Education, structured around central topics of the capabilities approach, to empower citizenship with such objective. The pedagogical proposals discussed here are as follows: (1) the conception of Higher Education Institutions from the approach of capability development, and aimed at social responsibility; (2) the formation of a university community as agents of their lives and communities; (3) the learning by the university community of the values in the capabilities approach; (4) the option of the university community for participation in public affairs in the pursuit of the common good; (5) the primacy of the formation of the university community as agents of sustainability agents.
Keywords: I24; I25; 650; Poverty; Relative poverty Spain; Higher education; Capabilities approach; Proposals against poverty